Transformation of The Prosecutor's Supervisory Function Through The Consultant and Catalyst Paradigm - Ryan Sumartha Syamsu; Amzulian Rifa’i; Iza Rumesten RS (Lembaga Bale Literasi, 2026)
The transformation of the internal supervisor of the prosecutor's office is important, from a watchdog to a consultant and a catalyst to improve the performance and reputation of the prosecutor's office. This study analyzes the implementation of internal supervision of the prosecutor's office from watchdogs to consultants and catalysts, as well as the concept of internal supervision of the prosecutor's office to become consultants and catalysts in the future. The normative legal research method is carried out both by researching literature materials in the form of laws and regulations, literature, comparison, and case studies. 5 The concepts of IIA and 6 directives contained in the Circular Letter of the Deputy Attorney General for Supervision Number B-69/H/HJW/06/2019 should be regulated in the provisions of Article 23 of the Attorney General's Regulation Number PER-022/A/JA/03/2011 concerning the Implementation of Supervision of the Prosecutor's Office of the Republic of Indonesia and Article 524 of the Attorney General's Regulation Number PER-006/A/JA/07/2017 concerning the Organization and Work Procedures of the Attorney General's Office of the Republic of Indonesia. So that the provisions of Article 23 and Article 524 can be added clauses, namely